Analysis of the Three-dimensional Transient Temperature Field of Rubber Parts of High Elastic Coupling - Lu Jinming; Liu Yun; Wen Huabing; Mao Nanmin; Zhang Pan (Jixie chuandong)
The temperature distribution of rubber parts of high elastic coupling will affect lifetime of product and reliability of the shaft system. The heat transfer theory and finite element method of uncoupling analysis is adopted to analyze the change process of temperature field of rubber parts and temperature change curve under dynamic torsion load. A dynamic thermal mechanical analysis is conducted,according to the relationship between damping factor and temperature,the loss analysis iteration is carried out. The temperature distribution test of rubber parts is performed on the torsion vibration test bench,the error of two calculation methods and measured values are compared and the validity of the numerical simulation method is verified. It is shown that the calculation accuracy of method which considering the temperature dependence of the damping factor is higher than method which assuming the loss factor is constant. On this basis,the allowable vibration torque of coupling is obtained,the theoretical basis for the performance monitor and design optimization is provided.